ANALISIS EFEKTIVITAS PEMBAYARAN TOL BERBASIS SINGLE LANE FREE FLOW (SLFF) DIBANDINGKAN DENGAN E-TOLL MELALUI KINERJA GERBANG TOL DAN PERSEPSI PENGGUNA - Akbar, Fahmi; Firman Setiawan; David; Bahtiar; Semuel Rorrong (Jurnal Jalan Jembatan, 2025)
Single Lane Free Flow (SLFF), known as “Let It Flo,” is a contactless toll payment system based on RFID technology developed by PT Jasamarga to reduce transaction time and queuing at toll gates. However, its implementation has not been fully effective due to low user adoption. This study aims to identify the implementation of SLFF, analyze vehicle flow, service time, service level, and delay time between the E-Toll and SLFF systems, as well as evaluate user perceptions toward the system. The analysis applies queuing theory using vehicle survey data collected at the Bekasi Timur 2 Toll Gate on January 13, 16, and 18, 2025, and questionnaires distributed to toll road users. The results show that SLFF is only used by four-wheeled light vehicles with a low adoption rate of two vehicles per hour compared to 343 vehicles per hour for E-Toll. Nevertheless, SLFF can reduce delay time by 0.6 seconds per vehicle and increase service capacity with a projected result of 6,000 vehicles per hour, significantly higher than the E-Toll system’s capacity of 957 vehicles per hour. The system eliminates queues and reduces congestion with a service intensity below one (ρ < 1), while users report improved safety and comfort due to non-stop and contactless transactions. The main challenges include limited infrastructure, restricted gate availability, ongoing application development, and limited technological information on the SLFF/Flo system. Therefore, infrastructure expansion, application improvement, and government support are essential to accelerate adoption and enhance the performance of the toll system in Indonesia. Kata Kunci: SLFF/Flo, arus kendaraan, waktu pelayanan, persepsi pengguna, kuesioner Keywords: SLFF/Flo, traffic flow, service time, user perception, questionnaire